The "timber box" effect for premium wines. (May 2020) - Sung, Billy; Crawford, Robert; Teah, Min; Stankovic, Michelle; Phau, Ian
Abstract: The present research aimed to examine the effectiveness of using luxurious external packaging boxes to improve customer perceptions towards premium wine. Consumers viewed images of wine presented in four types of packaging: (1) no box; (2) a plain wooden box; (3) a wooden box with explanatory text; and (4) a wooden box with both explanatory text and a transparent window; and completed a survey measuring product attitude, willingness to pay, perceived luxury, and perceived risk associated with the product. Results indicated all box types resulted in higher willingness to pay, and that the explanatory and transparent boxes were able to elicit significantly higher product attitudes than the plain box or no box at all. The positive effects of the transparent and explanatory boxes were fully mediated, or explained, by perceived luxury. Furthermore, the negative effects underlying the plain box conditions were partially mediated by perceived risk. The present study was the first to empirically investigate the psychological mechanisms responsible for the influence of packaging, and to examine how perceived product luxury and perceived risk underlie these effects. Managerial implications are discussed, and recommendations are provided for retailers.